Славистика в Эстонии и за ее пределами - Dulichenko, Aleksandr (Acta Slavica Estonica, 2013)
Acta Slavica Estonica is an international series of publications on current issues of Russian and other Slavic languages, literatures and cultures. This volume consists of three parts. The first part contains papers of the National Committee of Estonian Slavicists for the 15th International Congress of Slavicists in Minsk, Belarus, focusing on current problems in Slavic linguistics. Papers in the second and third part of the volume are dedicated to Slavic lexicology and lexicography, and the problems of Slavic syntax and translation studies, respectively. Papers are published in Russian, Czech, Polish, Slovenian, and Yugoslav-Rusyn.